2009
DOI: 10.1177/0886260509340534
|View full text |Cite
|
Sign up to set email alerts
|

Male Rape Victim and Perpetrator Blaming

Abstract: One of four possible vignettes manipulated by (a) level of rape myth contained within them (low vs. high) and (b) type of rape (stranger vs. acquaintance) was presented to participants followed by scales measuring victim blame, perpetrator blame, belief in a just world, sex-role egalitarian beliefs, and male rape myth acceptance. Victim blaming was predicted by male rape myth acceptance. Perpetrator blaming was predicted by male rape myth acceptance and sex-role egalitarianism. Differences were found in victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 31 publications
15
101
4
Order By: Relevance
“…It is known international journal of technoethics Volume 8 • Issue 1 • January-June 2017 that these attitudes give leniency towards the perpetrator whilst attributing greater blame upon the victim (Bohner et al, 2009;Sleath & Bull, 2009). This finding is supported by recent research by Hatcher (2016) who found that rape myth acceptance and victim infidelity were predictive of revenge porn victim blaming.…”
Section: Interpreting the Resultsmentioning
confidence: 99%
“…It is known international journal of technoethics Volume 8 • Issue 1 • January-June 2017 that these attitudes give leniency towards the perpetrator whilst attributing greater blame upon the victim (Bohner et al, 2009;Sleath & Bull, 2009). This finding is supported by recent research by Hatcher (2016) who found that rape myth acceptance and victim infidelity were predictive of revenge porn victim blaming.…”
Section: Interpreting the Resultsmentioning
confidence: 99%
“…Some traditional research indicates that victims of stranger rape are blamed more compared to victims of acquaintance rape (Calhoun, Selby, & Warring, 1976;Smith et al, 1976;Tetreault & Barnett, 1987). However, recent research indicates that victims are consistently blamed more when it concerns date and acquaintance scenarios, compared to stranger scenarios (Bell et al, 1994;Kelly, 2009;Sleath & Bull, 2010;White & Yamawaki, 2009;Yamawaki, 2009). This disparity most likely occurs because traditional and recent research utilize different types of scenarios, each with unique characteristics (regarding location, language use etc.…”
Section: Victim-perpetrator Relationshipmentioning
confidence: 98%
“…It has been hypothesized that observers holding stronger rape myth beliefs will blame victims more than people without such strong beliefs and research has consistently provided evidence for this correlation. Rape myth acceptance is found to be a significant predictor of rape victim blaming (Mason, Riger, & Foley, 2004;Yamawaki, 2009), and rape perpetrator blaming (Kopper, 1996;Sleath & Bull, 2010), with observers scoring high on rape myth acceptance tending to blame the victim more and the perpetrator less. Furthermore, observers with high levels of rape myth endorsement generally minimize the rape to a greater extent (Newcombe et al, 2008), and are less likely to believe that a rape has actually occurred (Mason et al, 2004), than people who endorse rape myths to a lesser extent.…”
Section: Rape Myth Acceptancementioning
confidence: 98%
See 1 more Smart Citation
“…Davies, Pollard, & Archer, 2006;Russell, Oswald, & Kraus, 2011). A significantly higher percentage of men compared to women believed that most raped men are somewhat to blame and 51% of men (compared to 19.4% of women) indicated that they would have a hard time believing a man who said that he was raped by a woman (Sleath & Bull, 2010). Similarly, a study on verbal coercion found that male participants attributed less distress and more pleasure to the victim, although no gender differences were found in ratings of male victim responsibility (Katz et al, 2007).…”
Section: Rape Myth Acceptancementioning
confidence: 99%